The Pacifgic Gondwana margin in the late Neoproterozoic-Early Paleozoic: Detrital Zircons U/Pb ages from in northwest Argentina reveal the maximun age, provenance and tectonic setting - Adams, Christopher (2011)
U–Pb detrital zircon ages are reported from Puncoviscana Formation (late Neoproterozoic–Early Cambrian) and Mesón Group (Late Cambrian) greywackes of northwest Argentina, to constrain provenance and depositional environment. The new data are combined with previously-published detrital zircon ages, to show that Puncoviscana Formation age patterns contain two broad groups: late Mesoproterozoic–early Neoproterozoic (1150–850 Ma) and late Neoproterozoic–Early Cambrian (650–520 Ma); with their relative proportions varying inversely with youngest component age. The 1150–850 Ma age components are dominant in greywackes with oldest late Neoproterozoic components > 600 Ma. The former diminish considerably when late Neoproteozoic components become dominant and younger, to 520 Ma. A northernmost greywacke sample from Purmamarca, Jujuy, is distinctive: whilst its zircon age pattern partly resembles other Puncoviscana Formation samples, it contains no Cambrian–late Neoproterozoic ages, the youngest ages being early Neoproterozoic. This may reflect an early, Neoproterozoic, passive-margin depocentre for the Formation, or an older (early Neoproterozoic) succession within it, which may predate the Brasiliano orogeny in Brazil. The youngest age components, c. 520 Ma, in a greywacke from Rancagua (Cachi, Salta province), dominate an almost unimodal pattern suggestive of contemporary volcanic sources at a late Early Cambrian depocentre. Detrital zircon age patterns of the Mesón Group (Lizoite Formation) have major Cambrian–latest Neoproterozoic components resembling those of the Puncoviscana Formation, but its Mesoproterozoic component is diminished, and there are no significant age components of this age. Small youngest components at c. 500 Ma suggest a maximum Late Cambrian stratigraphic age. The Puncoviscana Formation detrital zircon patterns suggest a provenance in a continental hinterland having a stabilised, extensive late Mesoproterozoic orogen (with minor Paleoproterozoic and Archean precursors), and a more variable late Neoproterozoic orogen containing an evolving sequence of less extensive subcomponents. A direct relationship with the Brazilian Shield is suggested; with sediment supplies originating within active-margin orogens of the interior and collisional orogens at the suture between African and South American cratons, but ultimate deposition in passive-margin environments of western Gondwanaland.